Generation of sub-nanosecond pulse in dual-wavelength praseodymium fluoride fibre laser. (28th August 2019) - Ahmad, H; Ahmed, M H M; Samion, M Z; Kamely, A A; Ismail, M F; Harun, S W; Thambiratnam, K
Abstract: In this paper, we demonstrate a stable dual-wavelength pulsed output from a praseodymium doped fluoride fiber laser. These dual functions are induced by intensity-dependent transmission and loss due to the cavity birefringence. The two lasing wavelengths centered at 1298.26 nm and 1299.91 nm with a spacing of 1.65 nm and a 3 dB bandwidth of 0.11 nm and 0.13 nm respectively are obtained. The pulse width induced by the dual-wavelength laser falls within the picosecond region, with a repetition rate of 389 KHz and a maximum average pulse energy of 5.4 nJ.